2018
DOI: 10.1002/tcr.201700067
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Storage in Porous Materials: Status, Milestones, and Challenges

Abstract: In this account the most relevant advancements in hydrogen storage in porous materials are presented. These include the current state-of-the-art, the challenges which have been overcome, and the hurdles which still remain. The most important milestones which will be discussed in this work will be the development of new apparatuses capable of delivering reliable results under a broad range of operational conditions, in which analysis temperature and pressure are critical parameters. Other aspects such as the ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 42 publications
1
46
0
Order By: Relevance
“…Both of them may result the low production of Fe 2+ . On the other hand, it indicated that the MIL‐101(Cr), based on its porosity and H 2 storage, could extend the retention time of H 2 in solution. That promoted the reduction efficiency of Fe 3+ by activating hydrogen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both of them may result the low production of Fe 2+ . On the other hand, it indicated that the MIL‐101(Cr), based on its porosity and H 2 storage, could extend the retention time of H 2 in solution. That promoted the reduction efficiency of Fe 3+ by activating hydrogen.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, the metal–organic frameworks (MOFs) material, with high specific surface area, tunable and large pore size, and diversity open metal sites, are showing great application potential of gas separation, sensing, energy storage and catalysis . Especially in the field of hydrogen storage, these properties facilitate the adsorption of H 2 on the surface of it.…”
Section: Introductionmentioning
confidence: 99%
“…The relative moderate hydrogen capacity of 4.4 wt.% might seem to be its weak point as compared to other LOHC [16]. However, its high density of 1.22 g/cm 3 leads to a volumetric capacity of 53 gH 2 /L, equivalent to an energy density of 1.77 kW·h/L, which is larger than the value of compressed hydrogen at 70 MPa [9,17].…”
mentioning
confidence: 88%
“…Formic acid (methanolic acid, HCOOH, FA), the simplest carboxylic acid (pK a = 3.75), is an outstanding LOHC candidate, which not only encompasses most of the features listed above but also, it is a product of the hydrogenation of CO 2 [14,15].The relative moderate hydrogen capacity of 4.4 wt.% might seem to be its weak point as compared to other LOHC [16]. However, its high density of 1.22 g/cm 3 leads to a volumetric capacity of 53 gH 2 /L, equivalent to an energy density of 1.77 kW·h/L, which is larger than the value of compressed hydrogen at 70 MPa [9,17].The production of H 2 from FA was firstly investigated by Coffey in 1967 [18], but it was not until 2008 when the interest of FA as a LOHC was renewed thanks to the independent investigations carried out by Laurenczy and Beller [19][20][21]. Along these years, studies dealing with the production of H 2 from FA have been carried out by using both, homogeneous and heterogeneous catalysts of diverse composition [22][23][24].…”
mentioning
confidence: 96%
See 1 more Smart Citation